(untitled) (Minerva. Revista de Filología Clásica, 2019)
We could say that Mycenaean adjectives in -we-sa and Arcadian Άνεμωσα come from *-went-ya, not from *-wet-ya, and that -sa (not **-za!) of feminine participle a-pe-a-sa is analogical of the participles with - Vnsa < *- Vntya. As another choice, we propose that Myc. pe-de-we-sa, a-pe-a-sa, Arc. Άνεμωσα, έασα, αισα, with *-VtyV> -V(s)sV> -VσV, could result from the same palatalization process which originated τόσος, όσος, etc.: palatalization would be acting in Pre-Mycenaean-Arcadian Greek with more strength and/or at an earlier stage than in other areas of East or South Greek.